Connecting South Asia and Southeast Asia: A Bangladesh country study - Mustafizur Rahman; Khondaker Golam Moazzem; Mehruna Islam Chowdhury; Farzana Sehrin (Asian Development Bank Institute (ADBI), 2014)
Economic integration is being inhibited by the poor state of transport connectivity between Bangladesh, and South Asia and Southeast Asia. This study reviews connectivity initiatives of Bangladesh and the two neighboring regions and proposes ways to deepen regional and interregional connectivity. Since the early 1990s, as a consequence of trade-led growth strategy, South Asia and Southeast Asia have emerged as important economic partners of Bangladesh both in terms of export destination and import sourcing. However, constraints "at the border" and "behind the border" have tended to undermine the prospects of reaping the benefits accruing from closer economic cooperation. There is now an increasing realization among policymakers in Bangladesh of the importance of transport integration as an effective tool for market integration and also for attracting efficiency-enhancing and market-seeking investment. This changed perspective has been reflected in Bangladesh's long-term development policies. This study identifies cross-border initiatives with Bangladesh's involvement particularly at the bilateral, subregional, and regional levels. Some of these initiatives are also integrated with Asia-wide broader connectivity particularly through the Asian Highway and Trans Asian Railway initiatives. Ongoing initiatives include construction and upgrading of multi-lane highways and railways, road and rail bridges, procurement of locomotives and wagons, and construction of internal container river ports. However, progress has been slow and cross-border transit still remains an unaddressed issue. A consensus among the concerned countries is needed with regard to standard operating procedures, harmonization of standards and customs procedures, and service charges and user fees for transit facilities. Additionally, significant investment will be required for trade facilitation and to upgrade border trade facilities at land ports, inland waterways, and sea ports. The study identifies five key areas where concrete action from major stakeholders is required: (i) mobilizing the necessary funds for building physical infrastructure; (ii) identifying and sequencing of priorities; (iii) cross-border coordination; (iv) building human resources to manage cross-border mega projects; and (v) building supply-side capacities to benefit from connectivity-driven regional market opportunities.
Keywords: F15; R42; 330; trade facilitation; cross-border movement of goods; vehicles; investments and services; regional connectivity